Case distribution and survival rate in Pediatric Intensive Care Unit (PICU) at Banjarmasin, Indonesia - Choirul Anam; Niarsari Anugrahing Putri; Rahmad Ramadhani; Yasmin Musfirah (Medical Faculty of Brawijaya University, Indonesia, 2022)
Introduction: Epidemiological studies about case distribution and survival in PICU is important to do. Knowledge of these epidemiological studies can assist in decision-making to improve patient quality of care. So far there is no data about the case distribution and survival rate of the patients in the PICU in Banjarmasin, Indonesia. This study aims to provide an overview of case distribution and survival rates of patients treated at the PICU of Ulin Hospital Banjarmasin. Methods: A retrospective study was conducted at the PICU of Ulin Hospital Banjarmasin. Data was taken from patients’ records from January 2017 to December 2018. Results: A total of 202 patients were admitted to the PICU, males 109 and females 93. The mortality rate was 17% with a survival rate, 83% with a mean length of stay of 10 days. The most common patient diagnosis was pneumonia 23%, meningoencephalitis 10%, and dengue shock syndrome 6%. The system commonly involved was respiratory system 26%, central nervous system 17%, and infection 13%. The median length of stay for overall admission was 9 days with a mean of 10 days. The cardiovascular and respiratory systems tend to have lower survival rates, 78%, and 79% respectively. Conclusions: This study shows that respiratory, neurological, and infectious diseases are the most common diseases that cause children to be admitted to the PICU. The mortality rate in this study was 17% with a mean length of stay of 10 days. It is necessary to focus on medical facilities and interventions to reduce respiratory-related mortality.